Stereotactic body radiotherapy vs conventionally fractionated chemoradiation in locally advanced pancreatic cancer: A multicenter case‐control study (PAULA‐1). (10th September 2020) - Arcelli, Alessandra; Buwenge, Milly; Macchia, Gabriella; Bertini, Federica; Guido, Alessandra; Deodato, Francesco; Cilla, Savino; Scotti, Valerio; Rosetto, Maria Elena; Djan, Igor; Parisi, Salvatore; Mattiucci, Gian Carlo; et al.
Abstract: Conventionally fractionated chemoradiation (CRT) or chemotherapy (CHT) are considered as standard options in locally advanced pancreatic cancer (LAPC) while stereotactic body radiotherapy (SBRT) is an emerging treatment in this setting. The aim of this study was to compare two cohorts of LAPC patients treated with SBRT ± CHT vs CRT ± CHT in terms of local control (LC), distant metastases‐free survival (DMFS), progression‐free survival (PFS), overall survival (OS), and toxicity. Eighty patients were included. Patients in the two cohorts were matched according to: age ≤/>65 years, tumor diameter (two cut‐offs: </≥3.0 and </≥3.9 cm), clinical tumor stage and clinical nodal stage, neoadjuvant CHT, and adjuvant CHT. Median prescribed total dose was 30.0 Gy (range: 18.0‐37.5) and 54.0 Gy (18.0‐63.0) in SBRT and CRT cohorts, respectively. Toxicity was evaluated by CTCAE v4.0 scale. Survival curves were calculated by Kaplan‐Meier method. For hypothesis testing an equivalence and a non‐inferiority test was calculated. No statistically significant differences in terms of acute and late toxicity, DMFS, PFS, and OS were recorded among the two cohorts. Median, 1‐, and 2‐year LC was: 16.0 months, 53.1%, and 40.5% in the CRT cohort and 22.0 months, 80.4%, and 49.8% in the SBRT cohort, respectively ( P : .017). A statistically non‐inferiority significance was recorded in terms of OS between CRT and SBRT ( P  = .031). Patients treated with SBRT showed higher LC rate and similar OS compared to CRT. Therefore, the design of confirmatory randomized studies comparing SBRT and CRT seems justified. Abstract : An equivalence of stereotactic body radiotherapy (SBRT) and chemoradiation (CRT) has been only suggested in some retrospective studies in pancreatic cancer (PC). This is the first matched case‐control study comparing SBRT and CRT in PC considering several endpoints. An equivalence in terms of overall survival, disease free survival, and metastasis free survival among the two treatments and an advantage of SBRT in terms of local control were recorded. Therefore, SBRT is almost comparable to standard CRT.